Low-cost communication system for explorer-class underwater remotely operated vehicle - Simon Siregar; Muhammad Ikhsan Sani; Muhammad Muchlis Kurnia; Dzikri Hasbialloh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Disaster recovery from underwater earthquake, plane crashes into the sea, and monitoring underwater cables or piping for energy purpose are underwater missions for Remotely Operated Underwater Vehicle (ROV) in ASEAN MATE 2018 Competition. Two essentials factor to perform successfully in this ROV competition are design of an efficient communication protocol system and a low-cost communication hardware. In this research, an optimal communication system between RS-232 serial communication transmission and RS-485 serial communication transmission is developed to obtain the optimal solution. Both communication system is tested in Tech_SAS ROV-Telkom University Indonesia, a microcontroller underwater ROV based which used single microcontroller to control actuator, sensor and communication, and measured the Quality of Services (QoS) for end-to-end delay and packets loss. From the the experiment and evaluation for the two schemes, shows 12.57 ms end-to-end delay, 0% data packet error and $6 RS-485 communication system are the optimal solution for Tech_SAS ROV.